Electroencephalographic characteristics of transcutaneous auricular vagus nerve stimulation for prolonged disorders of consciousness: a study protocol - Jiao, Haoyang; Zhai, Weihang; Zhang, Jinling; Xu, Long; Geng, Xiaoli; Chen, Xueling; Yang, Yi; Wang, Yifei (Frontiers in Neuroscience, 2025)
BackgroundIncreasing evidence indicates that transcutaneous auricular vagus nerve stimulation (taVNS) can promote the recovery of consciousness levels in patients with prolonged disorders of consciousness (pDOC). However, previous clinical studies have shown inconsistent clinical efficacy of taVNS in treating pDOC. This could be because no research has clearly defined the indications for taVNS treatment in patients with pDOC, and patients who were not indicated for taVNS treatment were included. Therefore, screening out the indications for patients with pDOC who are suitable for taVNS treatment is a key scientific issue that requires urgent resolution at present.Methods/designWe aim to incorporate 50 patients with pDOC into this study. All patients will undergo a 4-week taVNS treatment, and 30-min resting electroencephalogram (EEG) and Coma Recovery Scale-Revised (CRS-R) scores of each patient will be collected before and after the treatment. After the 4-week taVNS treatment, the patients will be followed up in the first, third, sixth, and twelfth months after the treatment. The 50 patients with pDOC will be classified into response and non-response groups based on whether their CRS-R scores increase. The differences in the brain power spectrum and functional connectivity of the EEG before enrollment between the two groups will be compared.DiscussionThe research objective of this experiment is to screen out the EEG characteristics of patients with pDOC who are suitable for taVNS treatment by using EEG technology, and lay the foundation for the wider application of taVNS in the treatment of patients with pDOC.Clinical trial registrationIdentifier ITMCTR2024000734, http://itmctr.ccebtcm.org.cn/.